Effect of alternative self-etch applications on dentin bond strength of "no wait concept" universal adhesives = Efecto de distintas alternativas de aplicación de los adhesivos universales con concepto de "no espera" en la resistencia adhesiva a la dentina - Serin Kalay, Tugba; Zaim, Beyza (2022)
This study evaluated the effects of alternative self-etch application modes on resin-dentin microtensile bond strength (μTBS) of three commercially available "no wait" concept universal adhesives. In this study extracted impacted non-carious human third molars were used. The flat surfaces were prepared in mid-coronal dentin and prepared with a 600-grit SiC paper. The three universal adhesives that were used are as follows: Clearfil Universal Bond Quick (CUQ, Kuraray Noritake, Japan), G-Premio Bond (GPB, GC Corp, Japan), and a self-curing universal adhesive "Tokuyama Universal Bond" (TUB; Tokuyama Dental, Japan). The following three different application procedures were used for the dentin surfaces: the adhesives were applied and immediately subjected to air-dry; the adhesives were applied followed by a 10-second wait; or the adhesives were rubbed for 10 seconds. Then composite resin was applied to the dentin surface and light cured. After storage in 37°C distilled water for 24 h, all the bonded teeth were cut into 1mm² sections using a low-speed diamond saw (Micracut 125 Low Speed Precision Cutter, Metkon, Bursa, Turkey) under running water (n=15). The sections were subjected to a tensile force at a crosshead speed of 1mm/min in a testing apparatus (Microtensile Tester, Bisco, IL, USA) and μTBS values were measured. Data were analyzed using the Kruskal-Wallis test and Mann-Whitney U test. Failure modes were analyzed under a stereomicroscope. Prolonged application time significantly affected the μTBS (p<0.005). A significant increase of μTBS on active application was observed for CUQ and GPB. The TUB with an active application had a significantly lower μTBS value compared with the other adhesives. Prolonged application time caused significant improvement of bond strength in all adhesives. The active application is effective at increasing the dentin bond strength except for TUB.
Este estudio evaluó los efectos de los modos alternativos de aplicación de adhesivos de autograbado en la resistencia de la unión microtensil entre resina y dentina (μTBS) de tres adhesivos universales de concepto "no espera" disponibles en el mercado. En este estudio se utilizaron terceros molares humanos impactados que fueron extraídos. Las superficies planas se prepararon en la dentina coronal media y se prepararon con un papel SiC de 600 granos. Los tres adhesivos universales que se utilizaron son los siguientes: Clearfil Universal Quick Bond (CUQ, Kuraray Noritake, Japón), G-Premio Bond (GPB, GC Corp, Japón), y un adhesivo universal autopolimerizable "Tokuyama Universal Bond" (TUB; Tokuyama Dental, Japón). Se utilizaron los tres procedimientos de aplicación siguientes para las superficies dentinarias: se aplicaron los adhesivos y se sometieron inmediatamente a un secado al aire; se aplicaron los adhesivos y se esperó 10 segundos; o se frotaron los adhesivos durante 10 segundos. Luego se aplicó resina compuesta a la superficie dentinaria y se fotopolimerizó. Después de su almacenamiento en agua destilada a 37°C durante 24 h, todos los dientes unidos se cortaron en secciones de 1mm² utilizando una sierra de diamante de baja velocidad (Micracut 125 Low Speed Precision Cutter, Metkon, Bursa, Turquía) bajo agua corriente (n=15). Las secciones fueron sometidas a una fuerza de tracción a una velocidad de cruceta de 1mm/min en una máquina de prueba universal (Microtensile Tester, Bisco, IL, USA) y se midieron los valores de μTBS. Los datos fueron analizados utilizando la prueba de Kruskal-Wallis y la prueba U de Mann-Whitney. Los modos de falla fueron analizados bajo un estereomicroscopio. El prolongado tiempo de aplicación afectó significativamente a los μTBS (p<0,005). Se observó un aumento significativo de μTBS en la aplicación activa para el CUQ y el GPB. El TUB con una aplicación activa tuvo un valor...
En revista Odóvtos, vol. 24, no.1 (enero-abril 2022)
Descripción basada en el contenido visto el 15 de noviembre, 2024
También disponible en formato HTML y EPUB